Rayleigh-Taylor instability under a flat beam - Lenschen, Matias (2010)
A theoretical and experimental study on the Rayleigh-Taylor instability of a thin liquid film is presented. The experiments were performed by coating the underside of a flat beam with uniform liquid film. The size of the beam is such that a linear arrangement of drops is formed allowing the measurement of the drops growth. The experimental growth of the drops has been compared to the results obtained from a stability analysis performed on the equation that controls the thickness evolution and an excellent agreement is found. In addition, both time and length scales of the phenomenon are established.